Crisis narratives in international law - Mbengue, Makane Moïse; D'Aspremont, Jean (Nijhoff law specials ;, 2022)
"Few would quibble with the idea that the SARS-CoV-2 virus strain has caused a crisis that affects just about everybody on the planet. As lawyers active in the field of international law, our reading and teaching, writing and thinking, law-making and adjudication have been profoundly affected. These nineteen essays, individually and as a group offer a range of reactions and insights, touching on the impact on international law in its present incarnation and in a broader historic context, a snapshot on the state of thinking about international law. They offer a reminder too, as Benedict Kingsbury tells us, of the wisdom of others, of the Maori insight about our propensity to walk backwards into the future with our eyes on the past"--